Characterization and interannual variation of air quality in the city of Buenos Aires relative to the new WHO guidelines - Mosto, Caterina (2024)
The World Health Organization (WHO) updated its air quality guidelines in September 2021. The daily and annual mean concentrations of nitrogen dioxide (NO2) and particulate matter with a diameter of less than 10 µm (PM10) measured at the three air quality monitoring stations in the city of Buenos Aires frequently exceed the new WHO air quality guideline (AQG) levels in the period 2010-2019. A trend analysis reveals a significant decrease in the annual mean PM10 concentration of 1.6 µg m-3 yr-1 and a consistent reduction in the frequency of exceedances of the daily AQG of 1.6 % yr-1 at the urban background station. In contrast, NO2 concentrations show slight positive trends at all three monitoring sites that could become statistically significant as new data become available. For both pollutants, the strong linear relationships between annual mean concentrations and their daily exceedance frequencies suggest that the new annual AQG levels are stricter than their corresponding daily limits, although these results are sensitive to the data set used. On the other hand, daily average concentrations of carbon monoxide (CO) are below the new AQG, with slight non-significant positive interannual trends at two of the sites. When the daily hourly wind sequence is used as a classification variable, marked differences in the concentration levels of the three pollutants with different wind patterns are obtained, which are maintained over the years, highlighting the role of local sources in the trends. In some cases, pronounced interannual variations are observed with specific wind patterns, suggesting the impact of new or more intense sources from specific wind sectors. Further efforts in monitoring and in developing high-resolution pollutant emission inventories will contribute to understanding the causes of these variations and to assessing air quality across the metropolitan area.